PERCEPTION OF PHYSICAL EDUCATION, SPORTS AND HEALTH TEACHERS IN ELEMENTARY SCHOOLS TOWARDS INCLUSIVE PRACTICES: A CASE STUDY IN CENTRAL LOMBOK DISTRICT - Angga, Prayogi Dwina; Kardiyanto, Deddy Whinata; Indraswati, Dyah (PROGRES PENDIDIKAN, 2025)
This study aimed to determine the attitudes of physical education teachers towards the inclusion of students with physical disabilities or physical disabilities in physical education learning programs in Elementary Schools. This study uses a qualitative approach with a descriptive-analytical method. The subjects of this study were physical education teachers in Gugus 1 Praya Tengah; as many as 5 Physical Education, Sports, and Health teachers were directly involved in this study, consisting of 4 men and one woman with an average teaching experience of 12.5 years. The object of this study is the implementation of physical education learning programs in elementary schools, which are incredibly inclusive services for people with physical disabilities. Data collection techniques used in this study were interviews, observations, and documentation. The main instrument in this study was the interview guideline, while the additional instrument was the observation guideline. The research data analysis technique used the Miles and Huberman interactive analysis model. Teachers argue that physical education classes are a good place for developing students with disabilities. They realize that students with disabilities can get the same opportunity to participate in physical education programs and develop social skills. Teachers recognize that the seminars or professional training provided are very lacking. This study has significant impacts in encouraging ongoing training for physical education educators to improve their ability to implement inclusive education and in the development of adaptive curricula that meet the needs of students with special needs. This study also emphasizes the importance of stronger collaboration between teachers, parents, and other stakeholders. In addition, the findings of this study open up opportunities for further research in creating adaptive physical education learning models that are appropriate to the local context and can be used as guidelines for more efficient inclusive education policies and practices.